Heavy energy drink consumption is associated with risky substance use in young Swiss men (Swiss Medical Weekly, 2020)
OBJECTIVES Heavy consumption of energy drinks appears to pose a public health problem among young adults. This paper examines (i) the prevalence of chronic heavy energy drink use (consuming energy drinks more than once a day) and (ii) its associations with sociodemographic and health behaviour-related factors, especially substance use. METHODS We used multiple logistic regression analyses to examine the relationships between chronic heavy energy drink use and sociodemographic and health behaviour-related factors, based on cross-sectional data from 18–21-year-old men who took part in the “Young Adult Survey Switzerland” (YASS) in 2010/2011 (n = 10,345) and 2014/2015 (n = 9761). RESULTS Prevalence of chronic heavy energy drink use was high in both data sets: 7.5% of young adult men in Switzerland in 2010/11, and 6.0% in 2014/15, consumed energy drinks more than once a day. Chronic heavy energy drink use followed a social gradient: people with a low level of education were more likely to consume energy drinks more than once a day. Multiple daily energy drink consumption was associated with other unhealthy behaviours, especially substance use (smoking, alcohol consumption, use of tranquilizers or sleeping pills, use of painkillers). Among the strongest associations were the use of painkillers (odds ratio [OR] 5.23, 95% confidence interval [95% CI] 3.51–7.79) and tranquilizers/sleeping pills (OR 4.07, 95% CI 2.66–6.25). CONCLUSION Chronic heavy energy drink consumers are a significant population subgroup in Switzerland and are relevant for public health due to the co-occurrence of unhealthy substance use. This link and the close relationship between chronic heavy energy drink use and social class indicate the role of lifestyle in the emergence and distribution of energy drink consumption. Interventions that encourage chronic heavy energy drink consumers to make positive lifestyle changes may contribute to the prevention of unhealthy substance use.